(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Teaching the English language poses numerous challenges for educators across various educational contexts. This article explores common problems faced in English language teaching (ELT) and proposes practical solutions to enhance the learning experience and outcomes. By addressing issues such as large class sizes, lack of resources, student motivation, and cultural differences, this study aims to provide a comprehensive guide for educators to improve their teaching methodologies and strategies.